Foreign Listing Location: A Study of MNCs and Stock Exchanges in Eight Countries - Saudagaran, Shahrokh M.; Biddle, Gary C. (Journal of International Business Studies, 1995)
This study aims to enhance our understanding of multiple listings by addressing the where question related to foreign listings. It examines factors that influence firms' choices of foreign stock exchanges. Based on a sample of 459 internationally traded MNCs, with at least one foreign listing on one of nine major stock exchanges (in eight countries) at year-end 1992, we find strong evidence that foreign listing locations are significantly influenced by 1) financial disclosure levels, and 2) the level of exports to a given foreign country.